Influence of urban expansion allocated to morphometric characteristics in flood occurrences: case study in João Monlevade-MG (Research, Society and Development, 2020)
The present study aimed to analyze the influence of urban expansion combined with morphometric characteristics in flood occurrences, in the municipality of João Monlevade-MG. To measure and classify the morphometric characteristics and obtain a map of use and occupation within the basin, a database available on the Water National Agency (ANA) website and the Alos Palsar satellite images were used. Land use and occupation was divided into 6 classes. The vegetation area presented the highest percentage of the basin. For the basin morphometric characterization, using the ArcGis 10.3 software,  it was necessary to quantify the area, perimeters, length of the basin main channel and its vector lengths. With these data, the compactness coefficient (Kc), form factor (Kf), circularity index (Ic), slope indexes, Sinuosity index (Is), Altimetric amplitude (Hm), drainage density (Dd), channel hierarchy, total number of water channels in the basin and relief ratio (Rr) were calculated. The results showed that the Carneirinhoscreek watershed has an average natural susceptibility to the development of floods. However, through the analysis of land use and occupation, anthropic uses prevailed and  an increase of the urban expansion was noted. This tends to intensify flooding processes in the area.